Critical Success Factors of ICT Implementation in Vocational High Schools - Alam, RG Guntur; Hidayah, Agung Kharisma (Universitas Negeri Padang, 2025)
Implementing Information and Communication Technology (ICT) in Vocational High Schools (SMK) plays a crucial role in enhancing the quality of learning, improving administrative efficiency, and preparing students for a technology-driven workforce. However, its implementation still faces various challenges, such as limited infrastructure, the readiness of educators, and uneven policy support. This study aims to identify the Critical Success Factors (CSFs) in ICT implementation in SMKs and analyze the challenges and opportunities for its development. A qualitative approach was employed, utilizing interviews with teachers, school principals, and students from various vocational schools to obtain a comprehensive perspective on ICT adoption in vocational education. The findings reveal eight key factors contributing to the success of ICT implementation: infrastructure availability, teacher competence, the role of school principals, government policy support, student engagement, curriculum integration, digital ethics, and continuous evaluation and monitoring. The study concludes that the success of ICT implementation heavily depends on the synergy between schools, the government, and industry. Therefore, more effective strategies are needed to ensure equitable access to technology, enhance teacher competencies, and strengthen digital-based curricula to optimize ICT to produce competitive SMK graduates in the Industry 4.0 era